let G be Group; :: thesis: for H2, H1 being Subgroup of G holds
( H1 is Subgroup of H2 iff multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #) )

let H2, H1 be Subgroup of G; :: thesis: ( H1 is Subgroup of H2 iff multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #) )
thus ( H1 is Subgroup of H2 implies multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #) ) :: thesis: ( multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #) implies H1 is Subgroup of H2 )
proof
assume H1 is Subgroup of H2 ; :: thesis: multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #)
then A1: the carrier of H1 c= the carrier of H2 by Def5;
the carrier of (H1 /\ H2) = (carr H1) /\ (carr H2) by Def10;
hence multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #) by ; :: thesis: verum
end;
assume multMagma(# the carrier of (H1 /\ H2), the multF of (H1 /\ H2) #) = multMagma(# the carrier of H1, the multF of H1 #) ; :: thesis: H1 is Subgroup of H2
then the carrier of H1 = (carr H1) /\ (carr H2) by Def10
.= the carrier of H1 /\ the carrier of H2 ;
hence H1 is Subgroup of H2 by ; :: thesis: verum